Acute cholecystitis after urological surgery: A report of 11 cases in our department and a review of the literature. (May 2016) - Yokoyama, Hitoshi; Hara, Hiroaki; Ogawa, Teruyuki; Ishizuka, Osamu
Objective: Postoperative acute cholecystitis (PAC) after gastrointestinal surgery is considered to be a relatively common complication. However, PAC after urological surgery is extremely rare. Patients and methods: We conducted a retrospective review of 2583 patients who underwent urological surgery in our department from 2006 to 2014 to identify those who developed acute cholecystitis in the postoperative period. Results: Of the 2583 patients, 11 (0.4%) were diagnosed with PAC. The study population consisted of 10 (91%) men and one (9%) woman. Among them, five (45%) patients had acalculous cholecystitis. The median interval between the preceding urological surgery and the onset of PAC was 16 days (range, 3–39 days). Emergent cholecystectomy and/or gallbladder drainage was performed in eight (73%) cases. Although four (36%) patients developed septic shock and were treated in the intensive care unit, cholecystitis improved in all cases. One patient died of her underlying disease (adrenal cancer) two months after PAC. Conclusion: Most routinely performed urological surgeries can cause PAC. The symptoms of PAC may be masked in the postoperative period. Urologists must be aware of PAC and should not hesitate to perform further inspection and consultation with a gastroenterologist in cases in which it is suspected.